CoolEdu: um modelo multiagente para colaboração em ambientes descentralizados de educação ubíqua - Rabello Junior, Solon Andrade (Universidade do Vale do Rio do Sinos, 2010)
The recent use of mobile devices and the widespread adoption of wireless computer networks have stimulated mobile and ubiquitous computing research. In this context, education is being considered one of the main application areas. The ability to accurately track the learner’s position through a location system and the context awareness support allow the discovery of new pedagogical opportunities. Nowadays, there are several approaches to the organization of ubiquitous computing environments, even if the majority of them employ a centralized architecture. This approach brings some benefits, like easing the access to the learner profiles, but it also has some disadvantages intrinsic to the model, like scalability concerns and the physical separation between the learners and their profile data. This work proposes a collaboration model created for decentralized environments, capable of improving the learning process through the stimulus to the interaction between learners. This approach is modeled using agents, e
Keywords: computação móvel e ubíqua; redes sem fio; dispositivos móveis; mobile and ubiquitous computing; wireless; mobile devices; Ciências Exatas e da Terra